Infection risks of diarrhoea associated with wastewater and excreta use in agriculture in Vietnam - Phuc Pham Duc; Hung Nguyen-Viet; Odermatt, P.; Zurbrugg, C.; Zinsstag, Jakob (2012)
When untreated wastewater and excreta are used for agricultural production, enteric pathogens may be a primary hazard to human health through different routes of exposure, as in direct contact with wastewater and excreta while doing field work. A quantitative microbial risk assessment was conducted to predict the risk of diarrhoea related to the use of wastewater and excreta for agricultural production in Hanam province, Vietnam. A total of 173 wastewater and excreta samples were collected from 5 critical sampling points. Three pathogens were analyzed quantitatively: E. coli by the MPN and the protozoan parasites G. lamblia and C. parvum by immunofluorescent antibodies and microscopy. A survey with 235 households was conducted using a structured-questionnaire to assess people’s exposure to wastewater and excreta. The most hazardous exposures included direct contact with the Nhue River and pond water, field water and composted excreta during field work. The highest mean concentration of diarrheagenic E. coli (DEC) (6.3 x 108 MPN/100 ml) and C. parvum (30 oocysts/100 ml) was in household sewage; whereas G. lamblia was highest in composted excreta (119 cysts/gram). Estimated annual infection risks in all the exposures were much higher than the commonly proposed thresholds of 10-4, the estimated annual risks of diarrhea values were at least 3-fold greater than maximal risk of 10-3 pppy; and the annual burden of diarrhoeal disease was extremely greater than the health target of 10-6 DALYs recommended by WHO. The assessment indicated exceeded risks for G. lamblia, C. parvum and DEC infections among people exposed to wastewater and excreta. Study results are useful in developing an integrated strategy for pathogen management and public health control in the agricultural settings where wastewater and excreta are intensively used as irrigation water sources and fertilisers and where household wastewater is freely discharged into irrigation channels.